Pengembangan Buku Saku Berbasis Ideal Problem Solving terhadap Kemampuan Pemecahan Masalah pada Materi Bangun Ruang - Balqis, Puri Ratih; Sandie, Sandie; Jamilah, Jamilah (Indo-MathEdu Intellectuals Journal, 2024)
The aim of the research is to develop a Pocket Book based on IDEAL Problem Solving that is suitable for use by students. This research is Research and Development (R&D). The research design used is the ADDIE model which consists of five stages consisting of Analysis, Design, Development, Implementation and Evaluating. This research was conducted at Assalam Pontianak Middle School with the research subjects being 15 students in class VII B. The data collection tools used were expert validation sheets, teacher and student response questionnaires, and problem solving ability tests. The data analysis used is calculating the validity of the media with the minimum criteria of "valid", calculating the practicality of teacher and student response questionnaires with the minimum criteria of "practical, and effectiveness using posttest calculations of minimally effective criteria. Based on the results that have been described, it is concluded that the IDEAL Problem Solving-Based Pocket Book on Problem Solving Abilities is suitable for use in learning because it can help improve problem solving abilities. The validity level of the Pocket Book with a validity level of "very valid" reaches media validity of 92% and material validity of 91.55%, the practicality level of the Pocket Book with the practicality level of "practical" and "very practical" with a student response questionnaire score of 81.01% and the questionnaire teacher response was 92%, and the effectiveness level of the Pocket Book with an effectiveness level of "effective" reached an average of 83.2%